Legal Politics of the Sexual Violence Crimes Act in Indonesia: Political Configuration and Its Relevance to the Fulfillment of Human Rights - Riswandha Imawan; Moh. Muhibbin; Ahmad Bastomi; Aji Purnomo; Husni Mubarak (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2026)
Introduction: Sexual violence in Indonesia continues to increase, indicating serious challenges in the protection and fulfilment of human rights. Although sexual violence is internationally recognised as a grave violation of human rights under the Rome Statute of 1998, the provisions of the former Criminal Code were inadequate to address its complex and diverse forms, thereby necessitating comprehensive legal reform. Purposes of the Research: This study aims to analyse the legal politics of the Sexual Violence Crimes Act by examining the political configuration underlying its formation and its relevance to the fulfilment of human rights. Methods of the Research: This study uses normative legal research with secondary data based on literature studies and qualitative analysis, combining a legislative and conceptual approach as well as legal policy analysis. Results Main Findings of the Research: The study finds that the Sexual Violence Crimes Act was shaped by a democratic political configuration that enabled strong public participation, resulting in a responsive and victim-oriented legal framework. This research contributes by demonstrating a direct link between political configuration and the law’s effectiveness in fulfilling human rights, positioning the Sexual Violence Crimes Act as a transformative, human rights-based legal reform in Indonesia.